The Routledge handbook of the English writing system - Cook, Vivian 1940-; Ryan, Des (Linguist) (Routledge Handbooks in Linguistics, 2016)
"The Routledge Handbook of the English Writing System provides a comprehensive account of the English Writing System, not just as a state of the art but also highlighting the developing trends that will influence its future. While concentrating on the core linguistic and psychological aspects, it will also include areas from such other disciplines as typography and computer mediated communication. Divided into five sections, the volume encompasses a wide range of approaches and addresses issues in the following areas: - The history of the English writing system - Acquisition and teaching - The English writing system in the media and CMC - Variety and diversity in the writing system - The core of the English writing system today Each of the thirty chapters is written by a specialist in the field and provides: a introduction to the subject; an overview of the main current and critical trends; and possible future tragectory. The Routledge Handbook of the English Writing System is essential reading for researchers and postgraduate students working in this area"--Provided by publisher.